2003
DOI: 10.1046/j.1095-8649.2003.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activities and pH variations in the digestive tract of gilthead sea bream

Abstract: Two investigations were carried out with 150 g gilthead sea bream Sparus aurata to determine the relative activity of six digestive enzymes (pepsin, trypsin, chymotrypsin, carboxypeptidase A, carboxypeptidase B and amylase) and the pH variation in the lumen of different parts of the gut of fish fed one or two meals per day. Pepsin activity was found exclusively in the stomach, whereas activities of the other enzymes studied were found in all regions of the gut, including the stomach. The lack of localization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
63
0
22

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 28 publications
(38 reference statements)
17
63
0
22
Order By: Relevance
“…On the other hand, Uys & Hecht [43] found higher activity of trypsin in the more posterior parts of the intestine of African catfish Clarias gariepinus (Burchell). In our study, no significant variation of chymotrypsin activity was found between different sections of the intestine, which tallies with the findings of Degura et al [41].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, Uys & Hecht [43] found higher activity of trypsin in the more posterior parts of the intestine of African catfish Clarias gariepinus (Burchell). In our study, no significant variation of chymotrypsin activity was found between different sections of the intestine, which tallies with the findings of Degura et al [41].…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, total protease and trypsin activity were the highest (P<0.005) in the proximal intestine, followed by anterior bulb, as compared to the rest of the segments. Higher trypsin activity in the upper part of the intestine has been reported in C. isheriensis [40], gilthead sea bream [41] and grass carp [42]. On the other hand, Uys & Hecht [43] found higher activity of trypsin in the more posterior parts of the intestine of African catfish Clarias gariepinus (Burchell).…”
Section: Discussionmentioning
confidence: 94%
“…Also, in these species, expressions and alterations of tryptic activity could be influenced by variations of abiotical factors such as salinity [76] and pH [77].…”
Section: Discussionmentioning
confidence: 99%
“…In fish, there are two different patterns for gastric acid secretion. One is characterized by maintenance of a neutral gastric pH during fasting (Deguara et al, 2003; Zhang et al (2013). Grey and black circle dots correspond to TP for stable isotope analysis (SIA) and for gut content analysis (GCA), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial knowledge of the GI tract in fish species has been documented in freshwater and marine fish: ontogeny of digestive functionality during larval stages (Walford and Lam, 1993;Yu et al, 2010;Ma et al, 2014), biochemical properties of digestive enzymes (Bitterlich, 1985;Chakrabarti et al, 1995;Deguara et al, 2003), morphological features (Wilson and Castro, 2010), and its relation to food habits and feeding (De Silva et al, 1980;Patricio Ojeda, 1986;Karachle and Stergiou, 2010). The postembryonic development of the digestive system is a key event in the life history of fish.…”
Section: Introductionmentioning
confidence: 99%